Galaxy clustering in the DESI Legacy Survey and its imprint on the CMB. Issue 1 (3rd December 2020) - Hang, Qianjun; Alam, Shadab; Peacock, John A; Cai, Yan-Chuan
ABSTRACT: We use data from the DESI Legacy Survey imaging to probe the galaxy density field in tomographic slices covering the redshift range 0 < z < 0.8. After careful consideration of completeness corrections and galactic cuts, we obtain a sample of 4.9 × 10 7 galaxies covering 17 739 deg 2 . We derive photometric redshifts with precision σ z /(1 + z ) = 0.012−0.015, and compare with alternative estimates. 1 Cross-correlation of the tomographic galaxy maps with Planck maps of cosmic microwave background (CMB) temperature and lensing convergence probe the growth of structure since z = 0.8. The signals are compared with a fiducial Planck ΛCDM model, and require an overall scaling in amplitude of A κ = 0.901 ± 0.026 for the lensing cross-correlation and A ISW = 0.984 ± 0.349 for the temperature cross-correlation, interpreted as the integrated Sachs–Wolfe effect. The ISW amplitude is consistent with the fiducial Λ cold dark matter (ΛCDM) prediction, but lies significantly below the prediction of the AvERA model of Rácz et al., which has been proposed as an alternative explanation for cosmic acceleration. Within ΛCDM, our low amplitude for the lensing cross-correlation requires a reduction either in fluctuation normalization or in matter density compared to the Planck results, so that $Ω _ m^{0.78}σ _8=0.297± 0.009$ . In combination with the total amplitude of CMB lensing, this favours a shift mainly in density: Ωm = 0.274 ± 0.024. We discuss the consistency of this figure with alternative evidence. A conservative compromise between lensing and primary CMB constraints would require Ωm = 0.296 ± 0.006, where the 95 per cent confidence regions of both probes overlap.